Strengthening soil health under rice (Oryza sativa) fallows in Eastern Plateau of India with dwarf rice and moisture conservation practices - SINGH, R N; PRAHARAJ, C S; KUMAR, RAHUL; SINGH, S S; KUMAR, N; SINGH, UMMED (The Indian Journal of Agricultural Sciences, 2018)
There is great scope in converting rice (Oryza sativa L.) fallows into productive agro-ecosystems through appropriate crop based interventions involving suitable varieties and appropriate resource conservation technologies (RCTs). Pulses such as chickpea, lentil, lathyrus and blackgram -through rotation or relay with rice - are the candidate crops for efficient utilization of conserved and scarce resources including soil moisture. Therefore, studying bio-physical aspects of popular rice - chickpea rotation so as to conserve resources and deriving maximum benefits is important and is the crux of the current investigation. A study was carried out in a vertisols at Indira Gandhi Krishi Vishwavidyalaya, Raipur (India) during 2011-14 under the existing conditions guarded by a tropical sub-humid climate receiving an annual precipitation of 1582 mm. Two transplanted rice habit groups (a tall local rice Masuri, maturing at 130-140 days and a dwarf HYV of rice Swarna, with 110-120 days duration grown during rainy season) were combined with three residue management practices, viz. residue removal, stubble (30 cm) and mulch for growing two contrasting varieties of chickpea (early high biomass JG 130 and medium high biomass JG 226) grown during winter season. Chickpea was planted with a zero till drill after rice. The study showed that soil moisture depletion (SMD) pattern was decreased over the crop season in case of mulched or 30 cm stubble retained plots in comparison to absence of mulch due to its possible role as a soil cover. On the contrary, SMD was higher in case of tall rice (Masuri) habit due to its relatively longer duration as compared to dwarf rice (Swarna) habit. Similar although to a lower degree in SMD was apparent in case of early biomass accumulating variety (BAV) chickpea JG 130 over medium BAV JG 226. Soil health parameters in terms of its physical and microbiological parameters (like, bulk density, soil strength, dehydrogenase activity etc), crop physiological parameters (such as relative leaf water content (LWC) and specific leaf weight (SLW), plant population), nodulation activities (Rhizobium population, nodule number and its dry weights) and crop growth/yield parameters (pods/plant, root characteristics etc) were positively influenced by mulch or stubble retention (due to its beneficial role as a soil cover) and dwarf rice habit (Swarna). Small yet consistently superior values of soil fertility indicators, viz. soil organic carbon (SOC) and nutrients (NPKZn, Fe, Mn and Cu) availability status were also evident following mulch or retention of stubble on the soil surface, whereas the values were abysmally small when comparison was made between chickpea cultivars (early BAV JG 130 and medium BAV JG 226). Besides these, weed dynamics, grain yield attributes and the resultant grain yield were especially favoured following soil moisture conservation strategies involving dwarf rice habit and mulch/stubble retention since availability of soil moisture was fairly extended over a period of time following these measures. Thus, it is inferred from the study on rice-chickpea system that efficient agronomic management of soil and land resources is crucial for augmenting soil health and enhancing output in prevalent rice fallow of Eastern Indian Plateau.